Physical activity interventions in children and young people with Type 1 diabetes mellitus: a systematic review with meta-analysis - Quirk, Helen; Blake, Holly; Tennyson, R.; Randell, T.L.; Glazebrook, C. (Wiley, 2014)
Aims